Covering the 2019 Hong Kong Protests - Luqiu, Luwei Rose. author. aut Link
V, 142 p.
Keywords: This book explores the impact of governmental, institutional, and individual factors on journalists covering protests, using the 2019 Hong Kong Anti-Extradition Bill Movement as a case study. The discussion surveys the challenges frontline journalists have faced while covering protests that unfolded in complex and rapidly evolving geopolitical contexts and media ecologies. Complementing this is an analysis of the Chinese government’s efforts to suppress social movements by curtailing press freedom to silence criticism of the government and keep information about the protest efforts from the public. Separate chapters explore these issues from the perspectives of the citizen journalists, student journalists, and independent journalists who have played key roles in the most recent social movements in Hong Kong. It concludes with a look at the future of press freedom in the city after the passage of the National Security Law. .